Use of the SAND balloon catheter in single‐incision laparoscopic cholecystectomy for acute cholecystitis. Issue 2 (22nd April 2013) - Ikegami, Toru; Shirabe, Ken; Yoshizumi, Tomoharu; Kayashima, Hiroto; Maehara, Yoshihiko
Abstract Introduction SILS for acute cholecystitis is technically challenging because of the difficulties in obtaining optical surgical field. Materials and Surgical Technique A 2‐cm incision was made through the umbilicus, a single port and trocars were introduced, and the abdomen was then insufflated. A 5‐mm SAND balloon punctured the abdominal wall and then the gallbladder wall. The distal and proximal balloons were inflated to prevent bile leakage, and the bile was aspirated. The collapsed gallbladder was then retracted cephalad, the critical structures were exposed, and the cystic artery and duct were divided. The gallbladder was dissected and removed through the umbilicus, and the abdomen was closed. We performed this procedure in three cases with acute cholecystitis. Operative times were 95, 133 and 244 min, blood loss was 5, 10 and 43 mL, and postoperative hospital stay was 2, 2 and 3 days, respectively. Discussion The single‐incision laparoscopic approach with the SAND balloon is a feasible technique for acute cholecystitis.